Relationship Between Transthoracic Echocardiography and Transesophageal Echocardiography in the Anatomic and Hemodynamic Assessment of Secundum Atrial Septal Defects in Children and Adults - Rehman, Mujeeb Ur; Sathio, Shahnawaz; Chand, Raam; Shaikh, Abdul Sattar; Ahsan, Aliya Kemal; Rehman, Fazal ur; Patel, Najma (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the relationship between transthoracic and transesophageal echocardiography in the anatomic and hemodynamic assessment of secundum atrial septal defects in children and adults.Study Design: Cross-sectional study.Place and Duration of Study: Department of Paediatric Cardiology, National Institute of Cardiovascular Diseases, Karachi Pakistan, from Jul 2020 to Jun 2021.Methodology: Seventy-seven patients above three years of age with secundum atrial septal defects were included. Linear regression was used to determine any statistically significant difference between transthoracic and transesophageal echocardiography approaches.Results: Of 77 patients, there were 37(48.1%) male and 40(51.9%) female. No significant difference was noted in terms of any of the clinical parameters during transthoracic echocardiography and transesophageal echocardiography. As per transthoracic echocardiography, 35(45.5%) were noted to be deviceable, while in transesophageal echocardiography, 36(46.8%) patients were found to be deviceable (p=0.872). No emergency exploration or deaths occurred. Linear regression showed no statistically significant difference between transthoracic echocardiogram and transesophageal echocardiography findings in terms of atrial septal defects size (p=0.226), total septal length (p=0.930), RV systolic pressure (p=0.440), RV functions and TAPSE (0.748) except LV ejection fraction function findings (p